Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Model Pembelajaran Think Pair Share Berbantukan Media Visual pada Peserta Didik Kelas III SDN 3 Palangka Tahun Pelajaran 2016/2017: Efforts to Improve Mathematics Learning Outcomes Using Think Pair Share Learning Models Assisted by Visual Media in Class III Students of Palangka Elementary School 3 in 2016/2017 Academic Year - Rizki Amalia; Karyanti Karyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to: (1) Know the learning activities of Mathematics class III students of SDN 3 Palangka Palangka Raya by using the Think Pair Share cooperative learning model Assisted by Visual Media. (2) Knowing whether or not there is an increase in Mathematics learning outcomes of third-grade students of SDN 3 Palangka Palangka Raya using Think Pair Share learning models Assisted by Visual Media. The research method used is Classroom Action Research (CAR) which seeks to solve or answer problems in learning. Subjects in this study were all third-grade students of Palangka Palangka Raya Elementary School 3, totaling 20 students divided into nine men and 11 women . Data collection techniques used are observation and tests. Data analysis techniques in this study are qualitative and quantitative. The results of this study indicate that: (1) Learning activities of third-grade students of SDN 3 Palangka Palangka Raya using Cooperative Learning models Think Pair Share Assisted by Visual Media more active with suitable criteria. (2) There is an increase in Mathematics learning outcomes by using the Think Pair Share cooperative learning model in third-grade students of SDN 3 Palangka Palangka Raya. The primary data learning outcomes reached an average value of 58 with classical data completeness of 25% and experienced an increase in the first cycle of an average value of 90 with a percentage of artistic data completeness of 100%.